PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERORIENTASI NILAI KEISLAMAN PADA MATERI PENGANGGURAN KELAS XI - Nur Kumala Sari; Siti Suprihatin (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
The objective of this research is to create the product of the Student Activity Sheet (LKPD) with Islam value oriented. This research uses research procedure and development 4D equipment model suggested by Thiagarajan and Semmel. This model consists of 4 steps those are Define, Design, Develop and Dissemination. However, in this research and development, the steps just done in develop step. The result of this expert testing toward design LKPD includes the suitable criteria with the percentage 87%, the result of the test in the material context of LKPD includes the suitable criteria with the percentage 78%, and the result of the test in the Islam value includes the suitable criteria with the percentage 90%. The test of respond by student with share the questionnaire showed with the percentage 89,4%.LKPD with Islam value oriented can be the one reference in the study of economic actually unemployment theory.